Anemia impact on non-fatal outcomes in chronic and acute coronary syndromes: results of local long-term registry. (14th October 2021) - Malinova, L; Radzhabov, K H; Dolotovskaya, P; Furman, N
Abstract:  : Anemia is the most common clinical condition worldwide known to increase risk of adverse cardiovascular events in patients with coronary heart disease. Randomized clinical trials often exclude patients with anemia and therefore do not offer accurate evidence about the effect of studied interventions and treatments on this population. At the same time, we need more evidence regarding anemia impact on non-fatal outcomes of coronary heart disease. The purpose of the study was to evaluate the impact of anemia on non-fatal outcomes of chronic and acute coronary syndrome and to assess prognostic value of hematological parameters. Methods: We used data of the local long-term registry of coronary heart disease with total number of patients 31 410. The registry contained data from patients admitted to intensive care unit (ACS-ICU) and cardiology department (CCS-in-hospital) of teaching hospital, emergency cardiology department of regular municipal hospital (ACS-ECD) and outpatient cardiology clinic (CCS-outpatient). In current analysis anemia was defined as hemoglobin (HB) level less than 120 g/L in both male and female patients. Data from patients with anemia at admission (n=598) were used in this analysis. Every cardiovascular event required admission or outpatient consultation was considered as non-fatal outcome. Median of follow-up period was 17 months. Results: Anemia in ACS was more severe that in CCS: HB in ACS-ICU 108 (100; 117) g/L vs 116 (109; 119) g/L in CCS-outpatient, p=0.002; and more frequently accompanied with leukocytosis (p=0.019) and thrombocytopenia (p=0.000). Despite those potentially unfavorable hematological finding ACS_ICU patients were characterized by the maximal amount of event-free patients during the follow-up period: 91.1% vs 87.0% (ACS-ECD) vs 76.5% (CCS-outpatient), Log Rank Mantel-Cox p=0.001, and maximal event-free time. The major difference between those health care facilities was in cardiologists' adherence to optimal medical therapy according to recent guidelines and frequency of antiplatelet prescriptions in anemic patients. We failed to detect significant hematological predictor of nonfatal adverse cardiovascular event in studied sample, at the same time logistic regression analysis demonstrated prognostic value of MPV (Wald 7.167, p=0.007), WBC (Wald 4.339, 0.037) and MCH (Wald 3.555, p 0.049) referring to event-free subpopulation. Similar results were obtained with classification tree method (7 nodes, 1st - MPV). Conclusion: In this registry involving CCS and ACS patients, presence of anemia had influence on clinical management and antiplatelet therapy. The type of health care facility was associated with non-fatal outcomes rate in anemic patients with ACS / CCS. The severity of anemia does not affect the risk of non-fatal cardiovascular events both in ACS and CCS patients; at the same time, inflammation and platelet production parameters could improve risk stratification in anemic patients with ACS and CCS. Funding Acknowledgement: Type of funding sources: None.